Oligomer nanoparticle release from polylactic acid plastics catalysed by gut enzymes triggers acute inflammation - Wang, Mengjing (2023)
The health risks of exposure to 'eco-friendly' biodegradable plastics of anthropogenic origin and their effects on the gastrointestinal tract are largely unknown. Here we demonstrate that the enzymatic hydrolysis of polylactic acid microplastics generated nanoplastic particles by competing for triglyceride-degrading lipase during gastrointestinal processes. Nanoparticle oligomers were formed by hydrophobically driven self-aggregation. In a mouse model, polylactic acid oligomers and their nanoparticles bioaccumulated in the liver, intestine and brain. Hydrolysed oligomers caused intestinal damage and acute inflammation. A large-scale pharmacophore model revealed that oligomers interacted with matrix metallopeptidase 12. Mechanistically, high binding affinity (Kd = 13.3 μmol l-1) of oligomers to the catalytic zinc-ion finger domain led to matrix metallopeptidase 12 inactivation, which might mediate the adverse bowel inflammatory effects after exposure to polylactic acid oligomers. Biodegradable plastics are considered to be a solution to address environmental plastic pollution. Thus, understanding the gastrointestinal fates and toxicities of bioplastics will provide insights into potential health risks.